Economic Security Formation of Enterprise Under the Conditions of Steady Development - Hryvkivska, Oksana; Kotvytska, Nataliia; Ivanova, Natalia; Pryimak, Nataliia; Salkova, Iryna (European Journal of Sustainable Development, 2021)
The most relevant aspects of achieving economic security of enterprises are determined in the article. The assessment of the level of economic security was conducted using the method of analysis of the functioning environment. The focal points of the assessment are interests, threats and resources. The possibility of economic security strengthening of business entities is traced using analysis of economic activity of mechanical engineering companies of Vinnytsia region of Ukraine as an example. At the same time, businesses that cannot cover the cost of resources with the income from goods sale in the current year were singled out. Businesses entities positioning in the functioning environment in the context of economic security motivation (interests - increase in enterprise income, threats - growth of current and long-term liabilities, resources - use of fixed assets and employees), allowed to find opportunities to increase the efficiency of enterprises that to the greater extent are related to the manufacturing of machinery and equipment.